Legal Protection for Lenders on the Transfer of Fiduciary Objects to Third Parties - Hamzah, Silvana Yasin; Lahaling, Hijrah; B, Sumiyati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine how Legal Protection for Lenders for the Transfer of Fiduciary Objects in the Form of Four-Wheeled Vehicles to Third Parties Without the Lender's Consent. This study uses an Empirical legal research method using a legal research method where empirical facts are taken from human behavior, both verbal behavior obtained from interviews and real behavior carried out through direct observation. Empirical research is also used to observe the results of human behavior in the form of physical remains or archives. The results of the study show; legal protection is an effort to provide protection to legal subjects, regarding actions that can be taken to maintain or protect the interests and rights of the legal subjects. Indonesia recognizes four material guarantee institutions, namely Pawn, Mortgage, Fiduciary, and Mortgage. One of the recognized guarantee institutions is fiduciary guarantee. Based on Law No. 42 of 1999 concerning Fiduciary Guarantees, it is explained that Fiduciary is the transfer of ownership rights of an object based on trust, where the object whose ownership rights are transferred remains in the control of the owner of the object.